The influence of real-time quantitative feedback and verbal encouragement on adults’ performance in maximal and explosive strength and power in bench press exercise - Pacholek, Martin (Frontiers in Physiology, 2024)
In sports practice, a wide array of verbal and non-verbal stimuli can elicit diverse motivations and performance changes. Therefore, the primary objective of this study was to compare the impact of various stimuli on maximal strength and power in bench press exercises. Methods: This study involved 48 university students (average age 20.5 ± 2.8 years; body mass 80.1 ± 20 kg; height 174.6 ± 6.7 cm; BMI 26.2 ± 6 kg/m2) who engaged in an 8-week resistance training program. The students were randomly divided into three experimental groups and one control group. The first group received real-time quantitative feedback (RF) on their power output during the bench press exercise, the second group received verbal encouragement (VE) from an instructor, and the third group exercised without any external stimulus (WS). The control group (CG) underwent only pre-and postmeasurements. To compare differences in strength parameters among groups a Two-Way Repeated Measures ANOVA was applied. Results: The results revealed significant improvements in the mean weight for one repetition maximum in the real-time quantitative feedback group (5 kg, 9.76%, p = 0.001, d = 0.529) and the verbal encouragement group (5.42 kg, 11.51%, p = 0.001, d = 1.201). Positive changes were also observed in the mean power at 20 kg and 30 kg for the RF, VE, and WS groups, but at 40 kg, significant improvement was only seen in the real-time quantitative feedback group (247 W, 31.30%, p = 0.001, d = 1.199). Conclusion: These findings underscore the effectiveness of selected stimuli in enhancing maximum strength and power during bench press exercises, with real-time quantitative feedback proving to be the most effective stimulus for improving both maximal strength and power.